Assuming the second term is (-x)2 rather than -(x2), there is no difference.
If the second term IS -(x2), then the difference is 2x2
Well, honey, when you multiply x by negative x, you get negative x squared. It's like math's way of saying "two wrongs don't make a right, they make a negative." So, in this case, x times negative x equals negative x squared.
x is negative 1x is negative 2
If you mean -(x^2) * x then the answer is -x^3 if you mean (-x)^2 * x then the answer is x^3
54.3 squared
-x times -x = x2 (negative multiplied with negative = positive) sqrt of x2 = x
It is: -2x squared
Negative 11
Let square = [x] -4+3*(-2)*[-4]+[3x-2x]=-4-6-2+[x]=-12+[x]The answer is negative 12 plus squared x.
x=3
I believe it would be 9, because negative three's negative would be 9 (double negative)
-(1/2)X^2 [negative half X squared]
It's equal to positive b squared, or (b x b) .